2018
DOI: 10.3390/ijerph15050993
|View full text |Cite
|
Sign up to set email alerts
|

Study of Factors Influencing the Bioaccessibility of Triazolone in Cherry Tomatoes Using a Static SHIME Model

Abstract: Estimating the influence of bioaccessibility of pesticide residues in fruits and vegetables on dietary exposure is a challenge for human health risk assessment. This study investigated the bioaccessibility of pesticide residues in cherry tomatoes and contributing factors (digestion time, pH, solid/liquid ratio, and dietary nutrition) using an in vitro test simulating the human gastrointestinal tract. pH had the largest effect on triazolone precipitation in the simulated gastric intestinal juice, which had a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Among the available gut models, SHIME is widely used due to (i) its automation, (ii) the possibility of sampling larger volumes more frequently (although this benefit comes with a requirement for large quantity of feed medium), (iii) the possibility of tightly controlling pH, temperature, and flow rate between the colon regions, (iv) the flexibility to configure multiple parallel units and different compartments, and (v) the possibility of performing longitudinal sampling in consecutive colon regions ( 14 , 21 , 22 ). While a majority of studies used SHIME to test the effects of drugs, xenobiotics, and supplements on in vitro microbial communities ( 21 , 23 26 ), it can also be used to study microbial ecology ( 27 , 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among the available gut models, SHIME is widely used due to (i) its automation, (ii) the possibility of sampling larger volumes more frequently (although this benefit comes with a requirement for large quantity of feed medium), (iii) the possibility of tightly controlling pH, temperature, and flow rate between the colon regions, (iv) the flexibility to configure multiple parallel units and different compartments, and (v) the possibility of performing longitudinal sampling in consecutive colon regions ( 14 , 21 , 22 ). While a majority of studies used SHIME to test the effects of drugs, xenobiotics, and supplements on in vitro microbial communities ( 21 , 23 26 ), it can also be used to study microbial ecology ( 27 , 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…their ability to penetrate into the body and be distributed among the tissues [ 125 ]. Several studies reported that bioavailability of pollutants can vary depending on pH and the type of the food being digested [ [126] , [127] , [128] ]. Pesticide sedimentation rate is significantly affected by the fat content of food [ 126 , 127 , 129 , 130 ].…”
Section: Transfer and Bioaccumulation Bioavailability Of Pesticidesmentioning
confidence: 99%
“…Several studies reported that bioavailability of pollutants can vary depending on pH and the type of the food being digested [ [126] , [127] , [128] ]. Pesticide sedimentation rate is significantly affected by the fat content of food [ 126 , 127 , 129 , 130 ]. The diet rich in fish and other foods of animal origin increases the effect of POPs compared to the diet rich in foods of vegetable origin [ 131 ].…”
Section: Transfer and Bioaccumulation Bioavailability Of Pesticidesmentioning
confidence: 99%
“…Indeed, in vitro upper and lower GI systems would help investigating the interactions of food chemical contaminants with main physicochemical parameters of the child digestive tract (low pH, enzymes, bile…), as well as resident gut microbiota (so called toxicomicrobiomics) (Abdelsalam et al, 2020;Sharma et al, 2017;Tralau et al, 2015). They would thus give useful information on the fate, bioaccessibility and metabolization (if any, especially by gut microbiota) of those compounds in the child gut, when ingested with different food matrices, taking also into account the role of soil that is frequently swallowed by infants (Defois et al, 2018(Defois et al, , 2017Joly et al, 2013;Liu et al, 2018;Yin et al, 2016). Lastly, all the potentialities of child in vitro models applied to food pollutants may be extended to food additives, e.g.…”
Section: Future Applicationsmentioning
confidence: 99%